2022
DOI: 10.3390/horticulturae8080740
|View full text |Cite
|
Sign up to set email alerts
|

Shoot Induction, Multiplication, Rooting and Acclimatization of Black Turmeric (Curcuma caesia Roxb.): An Important and Endangered Curcuma Species

Abstract: Curcuma caesia Roxb., commonly known as Kali Haldi or black turmeric, is one of the important species in the genus Curcuma. This species has been classified as one of the endangered Curcuma species due to the drastic decrement of this plant in its natural habitat. C. caesia has been overharvested for various purposes, including bioactive compound extraction to fulfill the pharmaceutical industry demand. Hence, this study was conducted to establish a protocol for the propagation of C. caesia via plant tissue cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Similar effects of mT on the height of micro-plantlets were reported by other researchers who studied various horticultural species (Moyo et al, 2018;Kucharska et al, 2020;Nowakowska et al, 2020). Other studies found that 2-ip might have different effects on the length of the microshoot, but for some tree crops, 2-ip can positively affect shoot growth compared to 6-BAP (Debnath;Kenneth, 2001;Faisal et al, 2006;Singh, 2020;Wulandari et al, 2021;Haida et al, 2022). The studied plant growth regulators could be arranged according to their effect on the ability to promote shoot formation in the following order: mT > 6-BAP > 2-ip.…”
Section: Shoot Multiplicationsupporting
confidence: 76%
“…Similar effects of mT on the height of micro-plantlets were reported by other researchers who studied various horticultural species (Moyo et al, 2018;Kucharska et al, 2020;Nowakowska et al, 2020). Other studies found that 2-ip might have different effects on the length of the microshoot, but for some tree crops, 2-ip can positively affect shoot growth compared to 6-BAP (Debnath;Kenneth, 2001;Faisal et al, 2006;Singh, 2020;Wulandari et al, 2021;Haida et al, 2022). The studied plant growth regulators could be arranged according to their effect on the ability to promote shoot formation in the following order: mT > 6-BAP > 2-ip.…”
Section: Shoot Multiplicationsupporting
confidence: 76%
“…Plant tissue culture is used for large-scale plant reproduction, virus elimination, secondary metabolite synthesis, and in vitro cloning (Ebrahimzadegan and Marou 2022; Haida et al 2022). Many studies have shown that the healing rate of Hemerocallis ower organs in tissue culture is higher than that of other parts, and the ower stem, scape, pedicel and petals are commonly used as explants (Wang 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Curcuma caesia Roxb. was successfully acclimatized in the potting medium by combining cocopeat and peat moss, producing the highest survival rate of 77.78% [10]. Success in acclimatizing tissue-cultured plants depends on factors like plantlet size and root condition, significantly affecting nutrient absorption [11].…”
Section: Acclimatization In Greenhousementioning
confidence: 99%